2021
DOI: 10.1073/pnas.2018140118
|View full text |Cite
|
Sign up to set email alerts
|

Observing ozone chemistry in an occupied residence

Abstract: Outdoor ozone transported indoors initiates oxidative chemistry, forming volatile organic products. The influence of ozone chemistry on indoor air composition has not been directly quantified in normally occupied residences. Here, we explore indoor ozone chemistry in a house in California with two adult inhabitants. We utilize space- and time-resolved measurements of ozone and volatile organic compounds (VOCs) acquired over an 8-wk summer campaign. Despite overall low indoor ozone concentrations (mean value of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
109
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 77 publications
(112 citation statements)
references
References 50 publications
2
109
1
Order By: Relevance
“…Liu et al 56 reported a similar finding from a detailed investigation of ozone-initiated chemistry in a normally occupied residence.…”
Section: Ozone Loss-rate Coefficient On Human Occupants (K H )supporting
confidence: 52%
“…Liu et al 56 reported a similar finding from a detailed investigation of ozone-initiated chemistry in a normally occupied residence.…”
Section: Ozone Loss-rate Coefficient On Human Occupants (K H )supporting
confidence: 52%
“…39 Liu et al have also showed that low ozone concentrations (~4 ppb) can generate detectable increases in multiple VOCs in a normally occupied residence, presumably because of ozonolysis of skin oil and surface films. 63 Along with 6-MHO and 4-OPA, they identified production of octanal, nonenal, nonanal, decanal, undecanal, and dodecanal, which together accounted for ≥12% of the consumed in- Declining per person emission rates of siloxanes were previously reported in a monitoring study conducted in a university classroom. 42 With respect to modeling indoor VOC emissions, time-dependent…”
Section: Emissions From Occupancymentioning
confidence: 75%
“…Furthermore, skin oils and their chemical constituents can be found on various indoor surfaces, such as glass, carpet and settled dusts. 66,67 NCA formation from human-ozone interaction may therefore be substantially more pronounced in real indoor…”
Section: Implications and Future Outlookmentioning
confidence: 99%